2015
DOI: 10.1002/ca.22545
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating sexual dimorphism in the human mastoid process: A viewpoint on the methodology

Abstract: The mastoid process is one of the most sexually dimorphic features in the human skull, and is therefore often used to identify the sex of skeletons. Numerous techniques for assessing variation in the size and shape of the mastoid process have been proposed and implemented in osteological research, but its complex form still presents difficulties for consistent and effective analysis. In this article, we compare the different techniques and variables that have been used to define, measure, and visually score se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
37
0
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 48 publications
0
37
0
11
Order By: Relevance
“…Selecting the particular landmarks to use is one of the most important tasks in the design of morphometric research projects and case studies. Even though landmark‐free approaches to shape analysis are gaining ground (Koehl and Hass, ; Bulut et al, ; Ghoneima et al, ), and even though non‐shape features such as volume and surface area remain relevant (Sholts et al, ; Shearer et al, ; Petaros et al, ), we believe that landmark‐based shape analysis will continue to be a very important research method. One clear advantage of landmarks, compared to landmark‐free approaches, is that it is relatively easy to establish anatomical equivalence or correspondence.…”
Section: Discussionmentioning
confidence: 99%
“…Selecting the particular landmarks to use is one of the most important tasks in the design of morphometric research projects and case studies. Even though landmark‐free approaches to shape analysis are gaining ground (Koehl and Hass, ; Bulut et al, ; Ghoneima et al, ), and even though non‐shape features such as volume and surface area remain relevant (Sholts et al, ; Shearer et al, ; Petaros et al, ), we believe that landmark‐based shape analysis will continue to be a very important research method. One clear advantage of landmarks, compared to landmark‐free approaches, is that it is relatively easy to establish anatomical equivalence or correspondence.…”
Section: Discussionmentioning
confidence: 99%
“…The asymmetry of the biface surfaces was computed by analyzing the digital 3D models with spherical harmonics, a mathematical extension of elliptic Fourier analysis into 3D space developed during the last decade [20]. Thus, we here continue our efforts to develop new ways to investigate archaeological material using 3D technology [5158]. With new mathematical tools available for analyzing 3D surfaces, it becomes natural to ask what kind of information can be obtained from respectively 2D contours and 3D surfaces [59].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, visual inspection employs an ordinal scale, which represents the most minimal to maximal expression of the mastoid (i.e., female, probable female, indeterminate, probable male, and male). In previous studies, the accuracy of sex classification using the two conventional methods was shown to be relatively high . For example, the correct classification rate of mastoid height was 85.7% in South Indian samples and 74.7% in Japanese samples .…”
mentioning
confidence: 96%